1966
DOI: 10.1111/j.1399-3054.1966.tb07071.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies on the Physiology of the Phycobiont and Mycobiont Ramalina ecklonii By

Abstract: The lichenized fungus and alga of the fruticose lichen Ramalini ecklonii were isolated into pure cultures. The ascospores of the fungus failed to germinate in less than five weeks incubation in spite of the use of a variety of cultural conditions. The fungus showed a considerable increase in growth on malt extract agar. Both organisms showed a marked tolerance for high concentrations of glucose although growth was quantitatively reduced. The fungus was able to use a variety of carbon and nitrogen sources as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

1967
1967
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…This fi gure is considerably less than that reported for other photosynthetic micro organisms (HOOGENHOUT & AMESZ, 1965). Fox (1965) showed that a Trebouxia phycobiont which was light saturated at 170 ft-c at 22°C. produced 39.4 III of O2 per mg dry wt per hr, while a free-living Chlorella, also light-saturated at 170 ft-c., produced 51.0 III O2• Fox (1967) found a comparatively rapid photosyn thetic assimilation by Trebouxia, which was in sharp contrast to the slow growth of this alga.…”
Section: Growth and Metabolismcontrasting
confidence: 45%
See 2 more Smart Citations
“…This fi gure is considerably less than that reported for other photosynthetic micro organisms (HOOGENHOUT & AMESZ, 1965). Fox (1965) showed that a Trebouxia phycobiont which was light saturated at 170 ft-c at 22°C. produced 39.4 III of O2 per mg dry wt per hr, while a free-living Chlorella, also light-saturated at 170 ft-c., produced 51.0 III O2• Fox (1967) found a comparatively rapid photosyn thetic assimilation by Trebouxia, which was in sharp contrast to the slow growth of this alga.…”
Section: Growth and Metabolismcontrasting
confidence: 45%
“…One method for accomplishing this involves fragmenting a thallus in a blender and centrifuging the resulting slurry differentially. The sediment composed of the algal cells is diluted and pipetted onto plates of mineral agar (Fox, 1966). Bold's Mineral Medium (DEASON & BOLD, 1960) Part I.…”
Section: Centrifugation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of another fruticose lichen, Ramalina ecklonii, Fox (1966) demonstrated the capacities of each symbiont to take up labeled extracts produced by the other in pure culture. However, neither was individually able to produce usnic acid found in the intact thallus.…”
mentioning
confidence: 99%
“…Isolation of both symbionts [12][13][14] was carried out by macerating the samples in a mortar with enough volume of the appropiate buffer containing 1 mM EDTA. Homogenate was centrifuged at lOOOxgr for 2 min and supernatant was again cen trifuged for 1 min and 30 s until the hyphal suspen sion becomes colourless.…”
Section: Introductionmentioning
confidence: 99%